Phase I study of temsirolimus in combination with cetuximab in patients with advanced solid tumours. (August 2017) - Hollebecque, A.; Bahleda, R.; Faivre, L.; Adam, J.; Poinsignon, V.; Paci, A.; Gomez-Roca, C.; Thery, J.C.; Le Deley, M.C.; Varga, A.; Gazzah, A.; Ileana, E.; et al.
Abstract: Background: Preclinical studies suggest synergistic antitumour effects of mammalian target of rapamycin (mTOR) inhibitor such as temsirolimus combined with anti-EGFR monoclonal antibody such as cetuximab. Methods: Temsirolimus (T) and cetuximab (C) were combined and escalated in cohorts of patients with advanced or metastatic solid tumours, respectively from 15 to 25 mg and 150–250 mg/m 2, until the maximum tolerated dose (MTD) was determined. Effort was made in the expansion cohort to enrol patients harbouring a molecular aberration in the human epidermal growth factor receptor (EGFR) and/or phosphoinositide 3-kinase (PI3K) pathways. Paired biopsies were optional to evaluate pathway modulation. Results: Among 39 patients enrolled, three experienced dose-limiting toxicities (DLTs): pulmonary embolism (C200 + T20), stomatitis (C250 + T20) and acneiform rash (C250 + T25). The weekly C 250 mg/m 2 and T 25 mg dose level was selected as the MTD. The most common treatment-related adverse events were: acneiform rash (97%), oral mucositis (82%), fatigue (59%), nausea (41%) and diarrhoea (36%). The median progression-free survival (PFS) and overall survival (OS) were respectively 2.0 months [95% CI: 1.8, 3.5] and 7.5 months [95% CI: 5.5, 11.9]. Among all patients, partial responses (PRs) and stable diseases (SDs) were observed in 2 (5.1%) and 18 patients (46.2%), respectively. The objective response rate (ORR) in patients with a molecular aberration was 2/14 (14%), versus 0/24 in those without molecular aberration. Conclusions: Combination of T + C showed significant but manageable toxicities. Due to modest clinical activity, further evaluation is not recommended. Molecular selection could potentially increase the objective response rate and should be implemented during drug development. Highlights: A dose escalation study of temsirolimus combined with cetuximab was conducted. The expansion cohort included patients with aberration in the EGFR, PI3K pathways. The cetuximab 250 mg/m 2 and temsirolimus 25 mg weekly dose level was the MTD. The combination had modest clinical activity and significant toxicities. Molecular selection may increase the objective response rate.